Genetic and Clinical Predictors of Deep Brain Stimulation in Young‐Onset Parkinson's Disease. Issue 5 (18th January 2016) - Pal, Gian D.; Hall, Deborah; Ouyang, Bichun; Phelps, Jessica; Alcalay, Roy; Pauciulo, Michael W.; Nichols, William C.; Clark, Lorraine; Mejia‐Santana, Helen; Blasucci, Lucia; Goetz, Christopher G.; Comella, Cynthia; et al.
Abstract: Objective: In a cohort of patients with young‐onset Parkinson's disease (PD), the authors assessed (1) the prevalence of genetic mutations in those who enrolled in deep brain stimulation (DBS) programs compared with those who did not enroll DBS programs and (2) specific genetic and clinical predictors of DBS enrollment. Methods: Subjects were participants from 3 sites (Columbia University, Rush University, and the University of Pennsylvania) in the Consortium on Risk for Early Onset Parkinson's Disease (CORE‐PD) who had an age at onset < 51 years. The analyses presented here focus on glucocerebrosidase ( GBA ), leucine‐rich repeat kinase 2 ( LRRK2 ), and parkin ( PRKN ) mutation carriers. Mutation carrier status, demographic data, and disease characteristics in individuals who did and did not enroll in DBS were analyzed. The association between mutation status and DBS placement was assessed in logistic regression models. Results: Patients who had PD with either GBA, LRRK2, or PRKN mutations were more common in the DBS group (n = 99) compared with the non‐DBS group (n = 684; 26.5% vs. 16.8%, respectively; P = 0.02). In a multivariate logistic regression model, GBA mutation status (odds ratio, 2.1; 95% confidence interval, 1.0–4.3; P = 0.05) was associated with DBS surgery enrollment. However, when dyskinesia was included in the multivariate logistic regression model, dyskinesia had a strong association with DBS placement (odds ratio, 3.8; 95% confidence interval, 1.9–7.3; P < 0.0001), whereas the association between GBA mutation status and DBS placement did not persist ( P = 0.25). Conclusions: DBS populations are enriched with genetic mutation carriers. The effect of genetic mutation carriers on DBS outcomes warrants further exploration.